Changes between Version 3 and Version 4 of u/johannjc/scratchpad4
- Timestamp:
- 09/30/15 16:43:45 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad4
v3 v4 83 83 We can also write the equation as 84 84 85 $\beta = \alpha_0 T'_0 + \displaystyle \sum_{\pm i} \alpha_{\pm i} T'_{\pm \hat{i}} + \sum_{\pm i, \pm j,|i| \ne |j|} \alpha_{\pm i, \pm j} T'_{\pm \hat{i} \pm \hat{j}}$85 $\beta = \alpha_0 T'_0 + \displaystyle \sum_{\pm j} \alpha_{\pm j} T'_{\pm \hat{j}} + \sum_{\pm i, \pm j,|i| \ne |j|} \alpha_{\pm i, \pm j} T'_{\pm \hat{i} \pm \hat{j}}$ 86 86 87 87 and then work out the coefficients for the matrix equation 88 88 89 $\alpha_0 = -A -2E_{ ii}T_0^\lambda = n \kappa_\parallel \psi$89 $\alpha_0 = -A -2E_{jj}T_0^\lambda = n \kappa_\parallel \psi$ 90 90 91 $\alpha_{\pm i} = \pm C_iT^\lambda_{\pm hat{i}} + E_{ii}T_{\pm \hat{i}}^\lambda$91 $\alpha_{\pm j} = \pm C_jT^\lambda_{\pm \hat{j}} + E_{jj}T_{\pm \hat{j}}^\lambda$ 92 92